Cultural diversity, 'Living Law' and Women's Rights in South Africa - Albertyn, Catherine (Cambridge University Press, 2013)
This chapter considers the constitutional recognition of cultural diversity, especially as it is manifest through the recognition of customary law, and its relationship to the constitutional guarantee of gender equality. As the supreme law, the South African Constitution subjects all law (customary, common, and statutory) to the rights and values of the Constitution, including the primary democratic values of dignity, equality, and freedom. This chapter rejects the idea that the Constitution provides a “liberal democratic” framework that constitutes the basis for a “top-down” universalism that tests culture and custom against irretrievably external, liberal standards. Although the Constitution is capable of this, among other, interpretations, the chapter argues that the best – and most transformative – interpretation of the constitutional text is one that enables a deep respect for cultural identity and diversity and consequent recognition of positive cultural norms and practices, while also addressing cross-cutting, intragroup inequalities, such as gender. This interpretation recognizes that transformation under the South African Constitution requires courts to address multiple and intersecting inequalities, and that culture and custom – long ossified in official law – face particular challenges in adapting to contemporary political, economic, and social conditions. Although democratic and cultural values might be rooted in different contexts, South Africa’s history of colonialism, apartheid, and political struggles, as well as its socioeconomic development, mean that there is considerable common ground within and across communities for harmonizing customary law and the Constitution.
Keywords: Gender; Equality; Customary law; Women's rights